2020
DOI: 10.1177/1758835920936093
|View full text |Cite
|
Sign up to set email alerts
|

Novel strategies using modern radiotherapy to improve pancreatic cancer outcomes: toward a new standard?

Abstract: Pancreatic ductal adenocarcinoma (PDAC) remains one of the most aggressive solid tumours with an estimated 5-year overall survival rate of 7% for all stages combined. In this highly resistant disease that is located in the vicinity of many radiosensitive organs, the role of radiotherapy (RT) and indications for its use in this setting have been debated for a long time and are still under investigation. Although a survival benefit has yet to be clearly demonstrated for RT, it is the only technique, oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 173 publications
(308 reference statements)
0
41
1
Order By: Relevance
“…R0 resection was achieved in 13.9% of all included patients and 19.8% (25/126) of all those who completed the study treatment. These percentages are lower than those published in the literature [ 15 , 16 ]. After FOLFIRINOX ± chemoradiotherapy, Hosein et al., Nanda et al., Nitsche et al., Sadot et al., and Marthey et al.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…R0 resection was achieved in 13.9% of all included patients and 19.8% (25/126) of all those who completed the study treatment. These percentages are lower than those published in the literature [ 15 , 16 ]. After FOLFIRINOX ± chemoradiotherapy, Hosein et al., Nanda et al., Nitsche et al., Sadot et al., and Marthey et al.…”
Section: Discussioncontrasting
confidence: 72%
“…R0 resection was achieved in 13.9% of all included patients and 19.8% (25/126) of all those who completed the study treatment. These percentages are lower than those published in the literature [15,16] This variance in the proportions of patients with surgery and R0 resection can be attributed to differences in selection criteria between studies. In our trial, all patients were treated and observed prospectively.…”
mentioning
confidence: 67%
“…The pancreatic SBRT technique allows delivery of ablative doses in a highly conformational way, particularly at the tumor/vessel interface in few sessions (3 to 5), while reducing collateral damage to adjacent organs [4,5]. It can be easily integrated into a neoadjuvant approach, notably as an attempt to sterilize these tumor/vessels interface regions, contributing to a higher curative (R0) resection rate, as suggested by previous retrospective and phase I/II studies [6]. Insertion of inert radiopaque gold or polymerbased markers in or close to the tumor is a prerequisite for pancreatic SBRT treatments, allowing for precise targeting and real-time tracking of the tumor.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to chemotherapeutic protocols, radiotherapy is under investigation to “downstage” pancreatic tumors, delay recurrence and prolong patients’ survival [ 56 ]. However, chemoradiation often results in tumor repopulation, where residual tumor cells proliferate following radiation, causing relapse.…”
Section: Tumor Cells Evs-mediated Crosstalkmentioning
confidence: 99%